Sport concussion: Implications for the strength and conditioning professional - Pabian, P. S.; Greeno, E. D.; Heiden, M. V.; Hanney, W. (Strength and Conditioning Journal, 2013)
The topic of sport concussion is one of the most discussed issues in sports medicine over the past few years. All health care, medical, and strength and conditioning professionals should have a sound working knowledge of the developments on the topics of sports concussion because it is likely that all practitioners may encounter athletes, both competitive and recreational, with symptoms of concussion.